Analisa kepuasan dan keputusan penggunaan kembali teknologi mobile banking dengan pendekatan TAM - Suci Mulia Aristiana; Tommy Christian Efrata; Endi Sarwoko (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, Indonesia, 2025)
The development of information technology and digitalization has created great opportunities in carrying out digital innovation in the banking sector that makes it easier for customers to make transactions both self-service on digital applications and transactions made at branch offices. This study aims to analyze and explore satisfaction and decisions to reuse mobile banking application technology with the theory of technology acceptance (TAM) including Perceived Usefulness, Perceived Ease of Use, Perceived Trust, Perceived Security at PT. Bank Central Asia Tbk and contribute to improving BCA's digital services and enriching the literature on research studies related to the quality of digital services, customer satisfaction in the banking world. The background of this study was to determine how indicators (TAM) affect customer satisfaction and the reuse of mobile banking technology so that they can be used as evaluation material for improving applications and determining strategies to increase customer satisfaction through the development of application technology that can be adjusted to customer needs. The research methodology uses a quantitative approach with the unit of analysis being customers who transact using the BCA mobile application in the West Nusa Tenggara region. The research sampling technique was random sampling and data collection was carried out through a digital questionnaire. The results of the study indicate that Perceived Ease of Use and Perceived Security have a significant effect on the decision to reuse, while Perceived Trust and Perceived Usefulness do not have a direct effect. However, the three variables have a positive effect on satisfaction, which then mediates the effect on Decision to Use. This finding strengthens the extended TAM model and emphasizes the importance of security and satisfaction aspects in increasing the adoption of digital banking services. This study provides theoretical and practical contributions to the strategy for developing digital-based financial service technology, especially in the banking sector.